Russian Market of the Dissertation Services - КалимуллинТагир Равилович (Journal of Economic Sociology, 2010)
The goal of the paper is to analyze the reproduction mechanism of the dissertation services market in Russia. The first part of the paper is devoted to the key approaches to determine the dissertation research. Further on the problem of social embededness of the dissertation research is tackled. The considerable attention is given to the role of social networks. The institutional specifics of writing the dissertation are shown with the help of example of the exchange forms in the academic sphere.